Leading from within: Understanding the lived experience of Gen X school heads in a digitalized world - Ventura, Stephanie P.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
The issue that schools and school systems are dealing with nowadays is how to find, nurture, and maintain talented and committed leadership. For systemic change to occur, the leaders of tomorrow must be identified and developed. There is a need to change structures and redefine boundaries in order to fully utilize the leadership potential in schools (Beach, 2020). However, according to Werde (2023) Gen Xers have experienced difficulties in their quest for leadership roles due to a few major issues. First off, with only 20% of the workforce made up of members of their generation, they are the least represented. They are frequently referred to as "the forgotten middle child" in the workplace because of their smaller proportion and lack of majority, and the second obstacle to their ascent to top positions in organizations is their commitment to work-life balance. This study aimed at determining and understanding the leading from within: the lived experience of gen x school heads in a digitalized world. Specifically, this study determined the lived experiences of Gen X school heads in private schools in a digitalized world and to understand how Gen X being school heads in private schools face the demands and challenges in a digitalized world. The researcher employed the phenomenological research design to understand and describe the lived experience of Gen X school heads in a digitalized world. Phenomenological research focuses on describing what all the participants have in common as they face the demands and challenges brought by the digitalized world. The basic purpose is to reduce individual experiences with a phenomenon to a description of the over-all essence. The salient findings of the study are: as to the lived experiences of Gen X school in a digitalized world: Three themes emerged with regards to their experiences as Gen X school heads in a digitalized world. It was revealed in their experiences that open communication and shared responsibility are evident in their school through their leadership. Being open with suggestions and willing to accept criticisms are some of the helpful and vital characteristics that they have to ensure communication among the teachers. It was noted that they also emphasize the significance of collaboration through open discussion in resolving issues or problems and understanding others’ sentiments. Moreover, some of the challenges that most of the participants’ encounter includes negative attitudes of teachers and students; digital divide since not all have the same level of technological skills, generation gaps considering the diversity of learners and the gap between them and the teachers and the slow internet connection and availability of teaching resources that affect the delivery of quality education. In addition, they also experience ways on how to keep up with the technological advancement, with this they have peer tutoring, programs that develop their own and the teachers’ digital skills, and being up-to-date with the latest technological advancements.